Cultivating Connections for Sustainable Small-Scale Feed Production and Commercialization in Ethiopia - Ekule, Muluken; Wamatu, Jane; Rudiger, Udo; Ndibalema, Gloriana (International Center for Agricultural Research in the Dry Areas, 2024)
One of the major hurdles in livestock productivity has been the limited availability and high cost of concentrate feed in the local market. This scarcity has impeded the growth of the industry, leaving farmers struggling to meet the nutritional needs of their livestock. However, hope has arrived in the form of a groundbreaking innovation by the International Center for Agricultural Research in the Dry Areas (ICARDA) under the CGIAR Initiative on Mixed Farming Systems. ICARDA has donated small-scale feed processing machines, with a capacity of five tons per hour, to youth and women sheep fattening cooperatives, enabling them to produce concentrated livestock feed directly from their cropping systems